Legal Reasoning Hakim Majelis Hakim Konstitusi Mengenai Pemungutan Suara Ulang Pemilihan Bupati dan Wakil Bupati Serang (Studi Analisis Putusan Majelis Hakim Konstitusi Nomor 70/PHPU.BUP-XXIII/2025) - Figo Galih Pradopo (PT. Hasba Edukasi Mandiri, 2025)
One tangible manifestation of regional autonomy is the direct implementation of Regional Head Elections (Pilkada). However, in practice, Pilkada often gives rise to electoral result disputes, including in the 2024 Serang Regent and Deputy Regent Election. This study employs a normative juridical method and applies a case approach. The regulation of re-voting (PSU) in the Indonesian legal system is governed by the 1945 Constitution of the Republic of Indonesia, Law Number 10 of 2016, General Election Commission Regulation Number 17 of 2024, and Election Supervisory Body Regulation Number 9 of 2024. The legal reasoning analysis of the judges in Decision Number 70/PHPU.BUP-XXIII/2025 reflects the Constitutional Court Panel’s courage in protecting democracy and safeguarding the integrity of elections from abuse of power, particularly involving state actors and village officials who commit structured, systematic, and massive (TSM) violations. Therefore, the decision to hold a PSU is an appropriate step to provide justice and restore a tainted democratic process. Oversight by Bawaslu and the KPU must be tightened, accompanied by ongoing education on neutrality for village officials and community leaders. The Constitutional Court is expected to continue upholding a substantive justice approach in resolving election disputes, so that the principles of honesty, fairness, and transparency can be more deeply felt by the public.